Business Model Creativity: - Kristian Brøndum; Christian Byrge; Søren Hansen (Journal of Business Models, 2018)
This paper presents a model for feasibility testing of novel ideas for business model innovators. It suggests a five-step systematic involvement of non-domain-related knowledge intended to deliver more unique ideas that are feasible in the decision-making phase of business model innovation.